The Importance of Husbandary Management in Producing Better Quality of Duck Eggs - Adriell, Joimi; Ahmad Faris Farhan, Helmin; Gloria Vanetta, Dandy; Magdelina, Bellarina; Nur Jasreen, Junaidi; Hung Hui, Chung (UNIMAS Publisher, 2025)
Good farm husbandry methods are a crucial part of providing safe and high-quality food products. It includes all agricultural measures, from the effort of acquiring and raising healthy animals, to their well-being and finally milking or slaughter. Farm management is carried out in such a way that animals remain healthy through adequate, contaminant-free feed and water with optimal living conditions (Figure 3.1). Livestock is grown based on risk analysis, and these risks are controlled in order to guarantee safe food production. Proper records are kept for simple traceability.